Holey, anti-impact and resilient thermoplastic urethane/carbon nanotubes fabricated by a low-cost "vapor induced phase separation" strategy for the detection of human motions. (September 2020) - Guo, Tong; Li, Changgeng; Yang, Jinglei; Wang, Pengfei; Yue, Jianling; Huang, Xiaozhong; Wang, Jing; Tang, Xiu-Zhi
Abstract: It is a great challenge to develop a scalable and cost-effective strategy for fabricating porous polymer-based piezoresistive devices. Here we presented a sort of conductive porous thermoplastic urethane (TPU) composites incorporated with carbon nanotubes by a vapor-induced phase separation method. By the introduction of carbon nanotubes (CNTs), the TPU composite exhibits moderate electric conductivity and improved compressive property. TPU composites are demonstrated to be highly sensitive sensors for monitoring both compression and bending strain. The value of ΔR /R0 changed from 90.0 to 98.7% while the gauge factor varied from 1.98 to 9. Further study on the dynamic mechanical performances indicates the produced TPU composites are strain-rate sensitive and the addition of CNTs can improve the anti-impact performances of TPU foam. The strategy adopted to fabricate TPU/CNT composite will pave the way for the development of low-cost and wearable sensors in practical applications of health monitor and sports.